Evidence for an anomalous like-sign dimuon charge asymmetry - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (American Physical Society (APS), 2010)
We measure the charge asymmetry A of like-sign dimuon events in 6.1fb -1 of pp̄ collisions recorded with the D0 detector at a center-of-mass energy √s=1.96TeV at the Fermilab Tevatron collider. From A, we extract the like-sign dimuon charge asymmetry in semileptonic b-hadron decays: Aslb=-0.00957±0.00251(stat)±0.00146(syst). This result differs by 3.2 standard deviations from the standard model prediction Aslb(SM)=(-2.3-0.6+0.5)×10-4 and provides first evidence of anomalous CP violation in the mixing of neutral B mesons. © 2010 The American Physical Society.